The Development of Learning Innovations in Primary Schools Over a Decade: A Bibliometric Analysis - Fauzi, Wildan Nuril Ahmad; Santosa, Iqbal Saffariz; Setiawati, Yuli (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to comprehensively analyze the development of learning innovations in primary schools over the past decade (2014-2024) through a bibliometric approach. Using data retrieved from the Scopus database, this study explores publication patterns by year, country, affiliation, and document type, as well as identifying main topics, co-occurrence of keywords, and collaboration patterns between authors and institutions. The analysis showed that while the number of publications remained relatively stable, the relevance and impact of research in educational innovation remained significant, with high average citations reflecting its academic contribution. The main themes expressed include the dominance of “educational technology,” “teacher training,” and “collaborative learning,” emphasizing the importance of technology integration and improving teacher competencies in the effort to advance the quality of education. While progress has been made, challenges such as disparities in access to technology and variations in teachers' digital competencies remain obstacles to be overcome. The research emphasizes the need to strengthen international collaboration, develop more in-depth studies on the relationship between teacher training and technology adoption, and explore under-researched topics such as “gamification” and “heritage education” to enrich learning approaches. This review provides a comprehensive view of the dynamics of educational innovation and presents strategic recommendations for future educational policy and practice.